Oregon's Coordinated Care Organizations Increased Timely Prenatal Care Initiation And Decreased Disparities - Muoto, Ifeoma; Luck, Jeff; Yoon, Jangho; Bernell, Stephanie; Snowden, Jonathan M (Health affairs (Millwood, Va.), 2016)
Policies at the state and federal levels affect access to health services, including prenatal care. In 2012 the State of Oregon implemented a major reform of its Medicaid program. The new model, called a coordinated care organization (CCO), is designed to improve the coordination of care for Medicaid beneficiaries. This reform effort provides an ideal opportunity to evaluate the impact of broad financing and delivery reforms on prenatal care use. Using birth certificate data from Oregon and Washington State, we evaluated the effect of CCO implementation on the probability of early prenatal care initiation, prenatal care adequacy, and disparities in prenatal care use by type of insurance. Following CCO implementation, we found significant increases in early prenatal care initiation and a reduction in disparities across insurance types but no difference in overall prenatal care adequacy. Oregon's reforms could serve as a model for other Medicaid and commercial health plans seeking to improve prenatal care quality and reduce disparities.